Development of the Students’ Entrepreneurship in Building a Creative Economy - Abdur Rohim; Ilfi Nur Diana; Aunur Rofiq (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
Pondok Pesantren (Islamic Boarding School) is one of the non-formal education which was founded by ulama figures (kyai) as a place to gain religious knowledge. Currently, Islamic boarding schools have undergone many changes, these changes are marked by the inclusion of formal/general education in pesantren. The purpose of this study was to determine how the strategy of the entrepreneurial spirit in the Al-Khoirot Islamic boarding school environment, Malang Regency. The method used in this study is a qualitative research based on the philosophy of postpositivism. The results of this study conclude that the strategy for developing an entrepreneurial spirit in the Al-Khoirot Islamic boarding school is by direct assistance by caregivers and head of the board to students who have the will to learn skills. To develop the creative economy in the Al-Khoirot Islamic boarding school environment, students are given the task of making various forms of different and interesting skills.